Influence of complex treatment with quercetin inclusion on cytokine profile indicators in chronic nonviral hepatitis patients - V. P. Prysyazhnyuk (Kazimierz Wielki University, 2017)
The influence of treatment with quercetin inclusion on the clinical and biochemical course and the cytokine profile of chronic nonviral hepatitis patients have been studied. In addition to the basic therapeutic treatment quercetin intake led to the decrease in the cytolytic and cholestatic syndromes activities which were manifested by a faster regression of clinical signs of the disease. During two weeks of treatment chronic hepatitis patients who received quercetin in addition to standard treatment, showed decrease in proinflammatory tumor necrosis factor-α by 61,9% (p = 0,02) and a marker of early cardiovascular injury atrial natriuretic propeptide in the blood by 53,8% (p = 0,04). However, according to the data obtained, it is clear that for a complete correction of clinical manifestations of the disease, biochemical changes and the cytokine profile two-week appointment of complex treatment with quercetin inclusion is not enough, which requires longer administration of the chosen treatment course before the onset of persistent remission at the out-patient stage.